Reinforced and toughened composite polyethylene material for plastic pipe processing and preparation method thereof
By introducing specific ingredients and process treatments into the polyethylene plastic pipes, a composite polyethylene material with enhanced toughening is prepared, which solves the problems of insufficient mechanical strength, impact toughness and aging resistance of the polyethylene plastic pipes, and achieves the improvement of the multiple properties of the material.
Patent Information
- Application Number
- CN202411620303.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The mechanical strength, impact toughness and aging resistance of existing polyethylene plastic pipes need to be further improved.
Low-density polyethylene is used as the matrix, combined with glycidyl methacrylate, flame retardant, composite filler, reinforced elastomer, initiator and auxiliary additive, and melt-extruded through a twin-screw extruder to prepare a composite polyethylene material with enhanced toughening.
The tensile performance, impact toughness, aging resistance and flame retardant properties of composite polyethylene materials are significantly improved, making them more suitable for outdoor pipe processing and preparation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene material processing, in particular to a reinforced and toughened composite polyethylene material for plastic pipe processing and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry, plastic pipes have been widely used in water supply and drainage, gas transportation, agricultural irrigation, chemical industry and construction due to their light weight, corrosion resistance and easy installation. Polyethylene, as one of the most commonly used plastic pipe materials, has excellent processing performance and chemical stability, and is usually used as a basic raw material to prepare plastic pipes.
[0003] In the prior art, a Chinese invention patent with publication number CN112662111A discloses a reinforced polyethylene pipe material and a preparation method thereof, which is characterized in that the extremely high molecular entanglement density and toughness of ultra-high molecular weight polyethylene (UHMWPE) are utilized to graft reactive groups on the PE pipe material and the UHMWPE molecules respectively, and a simple and efficient reactive melt processing method is used to realize the reaction of the two-phase molecules at the interface, and a lower molecular weight UHMWPE (L-UHMWPE) is introduced to construct a viscosity gradient matching the polyethylene pipe material and the UHMWPE, construct a strong interaction between the molecules at the interface of the two phases, promote the diffusion of the interface molecules, form a high degree of molecular entanglement at the interface, obtain good interface compatibility, realize good dispersion of UHMWPE in the polyethylene pipe material matrix, and significantly improve the toughness of the polyethylene pipe material.
[0004] That is, the plastic pipe in the prior art constructs a polyethylene pipe material with high-density polyethylene and lower molecular weight UHMWPE to improve the interface compatibility between molecules. At the same time, in order to improve the impact toughness of the material, inorganic particles are also added to the polyethylene material. However, the compatibility of inorganic particles with polyethylene materials is poor, and it is difficult to disperse them evenly in the polyethylene material, resulting in the mechanical properties and impact toughness of the polyethylene material to be further improved. In addition, when installed and used outdoors, the plastic pipe will be exposed to the air environment. After high temperature and ultraviolet radiation, the plastic pipe will age, resulting in a decrease in the mechanical properties of the plastic pipe. The aging resistance of the plastic pipe needs to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a reinforced and toughened composite polyethylene material for plastic pipe processing and a preparation method thereof, so as to solve the technical problem in the prior art that the mechanical strength, impact toughness and aging resistance of polyethylene plastic pipes need to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: a reinforced and toughened composite polyethylene material for plastic pipe processing, comprising the following components by weight: 90-100 parts of low-density polyethylene, 8-12 parts of glycidyl methacrylate, 5-6 parts of flame retardant, 15-22 parts of composite filler, 20-30 parts of reinforced elastomer, 0.5-0.8 parts of initiator and 3-5 parts of auxiliary additives;
[0008] The flame retardant is N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine.
[0009] Furthermore, the initiator is composed of dicumyl peroxide and ammonium nitrate in a weight ratio of 4:1, the auxiliary additives are composed of a dispersant, a lubricant, a plasticizer and an antistatic agent in a weight ratio of 3:1:7:2, the dispersant is a stearate, the lubricant is one or more of ethylene bisstearamide, polyethylene wax, and microcrystalline wax, the plasticizer is a phthalate, and the antistatic agent is one or more of antistatic agent SN, antistatic agent TM, and antistatic agent SP.
[0010] Further, the reinforced elastomer is obtained by processing the following steps:
[0011] A1. Add the emulsion into the reactor and stir. Raise the temperature of the reactor to 65-75°C. Add the siloxane solution dropwise into the reactor. After the addition is complete, heat and react for 4-6 hours to obtain a polysiloxane emulsion.
[0012] A2. Under nitrogen protection, add mixed olefins and initiators to a reactor containing polysiloxane emulsion, increase the temperature of the reactor to 75-85°C, keep the reactor warm for 6-8h, and post-treat to obtain a reinforced elastomer.
[0013] Reinforced elastomer synthesis reaction formula 1:
[0014] Reinforced elastomer synthesis reaction formula 2:
[0015] Where:
[0016] The synthetic reaction mechanism of reinforced elastomer is:
[0017] In the process of preparing the reinforced elastomer, the siloxane solution is hydrolyzed and self-assembled in an emulsion environment to form a siloxane polymer of siloxane condensation. Under high-speed stirring and emulsion environment, the siloxane polymer is uniformly dispersed in the emulsion in a microspherical structure. The unsaturated olefin double bonds modified on the siloxane polymer molecules and the unsaturated double bonds on the mixed olefin molecules undergo free radical polymerization under the action of an initiator to form a polyolefin coating on the outside of the polysiloxane, thereby preparing a reinforced elastomer.
[0018] Further, in step A1, the amount ratio of the emulsion to the siloxane solution is 10mL:2-3g, the siloxane solution is composed of octamethylcyclotetrasiloxane, 5-hexenyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 5:2:1, the emulsion is composed of purified water, ethanol, sodium dodecylbenzenesulfonate, and dodecylphenol polyoxyethylene ether in an amount ratio of 10mL:3mL:0.3g:0.1g, and the stirring speed of the reactor is 600-800r / min; in step A2, the amount ratio of the polysiloxane emulsion, the mixed olefin and the initiator is 100 mL:15-18g:0.2-0.3g, the mixed olefins are composed of ethylene glycol dimethacrylate, modified siloxane, N-(4-aminophenyl) maleimide, butyl acrylate and oleylamine in a weight ratio of 2:3:4:5:2, the initiator is potassium persulfate, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is lowered to room temperature, a 5wt% calcium chloride solution is added to the reactor, stirred to break the emulsion, filtered, the filter cake is washed with purified water for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain a reinforced elastomer.
[0019] Furthermore, the preparation method of modified siloxane is: add 18methyl-1,17-dihydroxynonasiloxane and toluene into a nitrogen-protected reactor and stir, increase the temperature of the reactor to 50-60°C, add 3-isocyanate propylene into the reactor, keep the reaction temperature for 3-5h, and post-treat to obtain modified siloxane.
[0020] The synthetic reaction formula of modified siloxane is:
[0021] The synthetic reaction mechanism of modified siloxane is:
[0022] Under nitrogen protection, air and water vapor were isolated, and isocyanate group was used as the active reaction group to undergo condensation reaction with the hydroxyl group on the 18-methyl-1,17-dihydroxy-nonasiloxane molecule to replace the hydroxyl group on the 18-methyl-1,17-dihydroxy-nonasiloxane molecule, and unsaturated double bonds were formed on the siloxane chain segment to prepare modified siloxane. The mass spectrometry analysis data of the modified siloxane were: m / z: 850.2539 (100.0%), 851.2535 (45.7%), 852.2508 (30.1%), 851.2573 (28.1%), 852.2568 (12.9%), 853.25 03(12.2%),852.2531(9.3%),853.2541(8.5%),854.2476(4.0%),852.2606(3.8%),854.2537(3.4%),853.2564(2.6%),852.2582(2.5%),854.2499(2.2%),853.2602(1.7%),855.2472(1.4%),853.2577(1.2%),854.2575(1.1%),855.2510(1.1%),853.2526(1.1%).
[0023] Furthermore, the dosage ratio of the 18-methyl-1,17-dihydroxy-nonasiloxane and 3-isocyanate propylene is 1 mol:2.1 mol, and the dosage ratio of the 18-methyl-1,17-dihydroxy-nonasiloxane and toluene is 1 g:5 mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 80-90° C., and the solvent is evaporated under reduced pressure to obtain modified siloxane.
[0024] Further, the composite filler is processed by the following steps:
[0025] B1, adding calcium carbonate and magnesium hydroxide in a weight ratio of 3:1 into a ball mill, grinding, passing through a 100-mesh sieve, to obtain an inorganic mixed powder;
[0026] B2. Add the inorganic mixed powder, KH-550 and ethanol into the reactor and stir and disperse for 30-50 minutes. Raise the temperature of the reactor to 45-55°C, add the catalyst into the reactor, keep the temperature for 3-5 hours, and post-treat to obtain the composite filler precursor.
[0027] B3. Add the composite filler precursor, acid binding agent and chloroform into the reactor and stir. Lower the temperature of the reactor to 8-12°C, add 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution into the reactor, and after the addition is complete, keep the temperature for 30-50 minutes. Increase the temperature of the reactor to 40-50°C, keep the temperature for 8-10 hours, and perform post-treatment to obtain the composite filler.
[0028] The synthetic reaction formula of the composite filler is:
[0029] Where: It is an inorganic mixed powder particle.
[0030] The synthetic reaction mechanism of composite fillers is:
[0031] Under alkaline conditions, KH-560 hydrolyzes and reacts with active groups on the surface of inorganic mixed powder particles to form amino modifications on the outside of the inorganic mixed powder particles. Then, under low temperature conditions, the carbonyl carbon atom in the acyl chloride group on the 3,5-di(tert-butyl)-4-hydroxyphenylpropionyl chloride solution reacts with the nitrogen atom in the amino group to undergo nucleophilic addition reactions to generate amides and by-product hydrogen chloride, thereby modifying the composite filler precursor particles with 2,6-di-tert-butylbenzene. During the reaction, an acid-binding agent is used as a neutralizer for the by-product hydrogen chloride, which can promote the forward reaction on the one hand, and prevent the by-product from reacting with the inorganic mixed powder particles to consume the inorganic powder particles on the other hand.
[0032] Further, in step B2, the amount ratio of the inorganic mixed powder, KH-550, ethanol and catalyst is 5g:3g:40mL:10mL, the catalyst is 0.2-0.5mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain a composite filler precursor; in step B3, the composite filler precursor, acid binding agent, chloroform and 3,5-bis(tert-butyl)-4 The dosage ratio of the 4-hydroxyphenylpropionyl chloride solution is 5g:1g:40mL:7g, the acid binding agent is composed of sodium bicarbonate and triethylamine in a weight ratio of 1:2, the 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution is composed of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and chloroform in a weight ratio of 1:3, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter is filtered, the filter cake is washed with chloroform twice and then with purified water three times, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain a composite filler.
[0033] The present invention also provides a method for preparing a reinforced and toughened composite polyethylene material for plastic pipe processing: low-density polyethylene, glycidyl methacrylate, flame retardant, composite filler, reinforced elastomer, initiator and auxiliary additives are added to a twin-screw extruder for melt extrusion to obtain composite polyethylene.
[0034] Furthermore, the temperatures of the six temperature zones of the twin-screw extruder from the feed end to the discharge end are 1850°C, 190°C, 195°C, 195°C, 195°C, and 200°C, respectively, and the main shaft speed of the twin-screw extruder is 15-17r / min.
[0035] The present invention has the following beneficial effects:
[0036] 1. The reinforced and toughened composite polyethylene material for plastic pipe processing of the present invention is based on low-density polyethylene as a matrix, N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine as a flame retardant, polyolefin-coated polysiloxane to prepare a reinforced elastomer, specially treated calcium carbonate and magnesium hydroxide as composite fillers, and glycidyl methacrylate as a cross-linking aid. Under the action of an initiator, while promoting the cross-linking between olefin molecular chains through free radical addition reaction, it can also increase the cross-linking degree between molecules through ring-opening condensation between epoxy groups and active groups such as hydroxyl groups, amino groups, and imino groups, promote uniform mixing and cross-linking of various components with low-density polyethylene, enhance the interfacial bonding strength between molecules, and coordinate the various components to improve the tensile properties, impact toughness, aging resistance and flame retardancy of the composite polyethylene material.
[0037] 2. The reinforced and toughened composite polyethylene material for plastic pipe processing of the present invention is prepared by preparing a reinforced elastomer with a polysiloxane having high flexibility as a core and a polyolefin having good strength and rigidity as a shell in an emulsified environment, thereby constructing an effective stress transfer network in the composite polyethylene, improving the tensile fracture stress and tensile fracture strain of the composite material, and when the material is impacted, the reinforced elastomer can serve as an energy dispersion point to disperse the impact energy to a larger area, reduce the risk of local damage, and improve the impact toughness of the composite polyethylene. Both polysiloxane and polyolefin have certain UV resistance and heat aging resistance. By introducing N-(4-aminophenyl)maleimide into the polyolefin layer, the amino group and maleimide group in the N-(4-aminophenyl)maleimide molecule can capture free radicals and slow down the aging process of the material. The five-membered ring structure of the molecule has high thermal stability and large steric hindrance, which improves the high temperature resistance of the polyolefin material while improving its interaction with the surrounding polyolefin segments to form a tighter network structure.
[0038] 3. The reinforced and toughened composite polyethylene material for plastic pipe processing of the present invention is prepared by modifying an inorganic mixed powder composed of calcium carbonate and magnesium hydroxide. The amino group, hydroxyl group and other functional groups modified on the surface of the composite filler can form hydrogen bonds with the carbonyl group, ester group and the like in the low-density polyethylene molecular chain, thereby increasing the intermolecular force between the composite filler and the low-density polyethylene, promoting the uniform dispersion of the composite filler in the low-density polyethylene, providing the composite polyethylene material with higher rigidity and strength, enabling it to withstand greater external forces without breaking. The composite filler particles, as stress concentration points, can absorb and disperse impact energy, thereby increasing the impact toughness of the material. The imino group and hydroxyl group modified on the surface of the composite filler can undergo ring-opening condensation with the epoxy group. The cross-linking degree of the composite polyethylene material is improved, and the impact resistance of the material is further improved. The 2,6-di-tert-butylbenzene modified on the surface of the composite filler particles has good antioxidant properties. It is compounded with the reinforced elastomer to construct a good antioxidant system in the composite polyethylene material to improve the antioxidant properties of the material. In the composite polyethylene system, the composite filler and the flame retardant are coordinated, and the nitrogen and phosphorus elements in the flame retardant molecules are used as flame retardant elements. During the combustion process, oxygen and heat are isolated, thereby inhibiting the spread of flames. The composite filler decomposes at high temperature to produce flame-retardant gases such as water vapor, which further dilutes the concentration of combustible gases and reduces the combustion rate. A synergistic flame retardant effect is formed in the composite polyethylene material, and the flame retardant properties of the composite polyethylene material are enhanced. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The low-density polyethylene in the present application is selected from Sinopec Maoming, the product name is LLDPE Sinopec Guangzhou, the density is 0.918 g / cm, the melt flow rate is 2 g / 10 min, and the melting point is 122°C.
[0041] Example 1
[0042] This embodiment provides a method for preparing a reinforced and toughened composite polyethylene material for plastic pipe processing, comprising the following steps:
[0043] S1. Preparation of modified siloxane
[0044] Weigh: 685.4 g of 18methyl-1,17-dihydroxynonasiloxane and 3427 mL of toluene are added to a nitrogen-protected reactor with stirring. The temperature of the reactor is raised to 50°C. 174.5 g of 3-isocyanate propylene is added to the reactor. The reaction is kept warm for 3 hours. After the reaction is completed, the temperature of the reactor is raised to 80°C, and the solvent is evaporated under reduced pressure to obtain modified siloxane.
[0045] S2. Preparation of reinforced elastomer
[0046] Purified water, ethanol, sodium dodecylbenzene sulfonate, and dodecylphenol polyoxyethylene ether were uniformly mixed in a dosage ratio of 10 mL: 3 mL: 0.3 g: 0.1 g to obtain an emulsion;
[0047] Octamethylcyclotetrasiloxane, 5-hexenyltrimethoxysilane and ethyl orthosilicate are uniformly mixed in a weight ratio of 5:2:1 to obtain a siloxane solution;
[0048] Weigh: 500 mL of the emulsion was added to the reactor and stirred at a stirring speed of 600 r / min. The temperature of the reactor was raised to 65°C. 100 g of the siloxane solution was added dropwise to the reactor. After the addition was completed, the reaction was kept warm for 4 hours to obtain a polysiloxane emulsion;
[0049] Ethylene glycol dimethacrylate, modified siloxane, N-(4-aminophenyl)maleimide, butyl acrylate and oleylamine are uniformly mixed in a weight ratio of 2:3:4:5:2 to obtain a mixed olefin;
[0050] Weigh: 1000 mL of polysiloxane emulsion is added to a nitrogen-protected reactor and stirred, 150 g of mixed olefins and 2 g of potassium persulfate are added to the reactor, the temperature of the reactor is increased to 75°C, and the reactor is kept warm for 6 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, 300 mL of 5 wt% calcium chloride solution is added to the reactor, stirred to break the emulsion, filtered, the filter cake is washed 3 times with purified water and then dried, the filter cake is transferred to a drying oven at a temperature of 60°C, and vacuum dried to constant weight to obtain a reinforced elastomer.
[0051] S3. Preparation of composite fillers
[0052] Calcium carbonate and magnesium hydroxide were added into a ball mill in a weight ratio of 3:1, and the mixture was passed through a 100-mesh sieve to obtain an inorganic mixed powder;
[0053] Weigh: 100g of inorganic mixed powder, 60g of KH-550, and 800mL of ethanol, add them into a reactor and stir and disperse for 30min, raise the temperature of the reactor to 45°C, add 200mL of 0.2mol / L sodium hydroxide solution into the reactor, and keep the reaction for 3h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at 70°C, and vacuum dry it to constant weight to obtain a composite filler precursor;
[0054] Mix sodium bicarbonate and triethylamine in a weight ratio of 1:2 to obtain an acid binding agent;
[0055] 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and chloroform are uniformly mixed in a weight ratio of 1:3 to obtain a 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution;
[0056] Weigh: 100 g of composite filler precursor, 20 g of acid binding agent and 800 mL of chloroform, add into the reactor and stir, lower the temperature of the reactor to 8°C, add 140 g of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution into the reactor, after the addition is complete, keep warm for 30 minutes, raise the temperature of the reactor to 40°C, keep warm for 8 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake twice with chloroform and then three times with purified water, transfer the filter cake to a drying oven at 70°C, and vacuum dry to constant weight to obtain a composite filler.
[0057] S4. Preparation of composite polyethylene
[0058] Dicumyl peroxide and ammonium nitrate are uniformly mixed in a weight ratio of 4:1 to obtain an initiator;
[0059] Mix sodium stearate, ethylene bisstearamide, dimethyl phthalate and antistatic agent SN in a weight ratio of 3:1:7:2 to obtain an auxiliary additive;
[0060] Weigh out by weight: 90 parts of low-density polyethylene, 8 parts of glycidyl methacrylate, 5 parts of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, 15 parts of composite filler, 20 parts of reinforced elastomer, 0.5 parts of initiator and 3 parts of auxiliary additives, mix evenly to obtain a mixture;
[0061] The mixed material is added into a twin-screw extruder, the temperatures of the six temperature zones of the twin-screw extruder from the feed end to the discharge end are 1850°C, 190°C, 195°C, 195°C, 195°C, and 200°C, respectively, and the main shaft speed of the twin-screw extruder is 15r / min. The mixed material is melt-extruded through the twin-screw extruder to obtain composite polyethylene.
[0062] Example 2
[0063] This embodiment provides a method for preparing a reinforced and toughened composite polyethylene material for plastic pipe processing, comprising the following steps:
[0064] S1. Preparation of modified siloxane
[0065] Weigh: 685.4 g of 18methyl-1,17-dihydroxynonasiloxane and 3427 mL of toluene are added to a nitrogen-protected reactor with stirring. The temperature of the reactor is raised to 55°C. 174.5 g of 3-isocyanate propylene is added to the reactor. The reaction is kept warm for 4 hours. After the reaction is completed, the temperature of the reactor is raised to 85°C, and the solvent is evaporated under reduced pressure to obtain modified siloxane.
[0066] S2. Preparation of reinforced elastomer
[0067] Purified water, ethanol, sodium dodecylbenzene sulfonate, and dodecylphenol polyoxyethylene ether were uniformly mixed in a dosage ratio of 10 mL: 3 mL: 0.3 g: 0.1 g to obtain an emulsion;
[0068] Octamethylcyclotetrasiloxane, 5-hexenyltrimethoxysilane and ethyl orthosilicate are uniformly mixed in a weight ratio of 5:2:1 to obtain a siloxane solution;
[0069] Weigh: 500 mL of the emulsion was added to the reactor and stirred at a stirring speed of 700 r / min. The temperature of the reactor was raised to 70°C. 125 g of the siloxane solution was added dropwise to the reactor. After the addition was complete, the reaction was carried out at the temperature for 5 h to obtain a polysiloxane emulsion;
[0070] Ethylene glycol dimethacrylate, modified siloxane, N-(4-aminophenyl)maleimide, butyl acrylate and oleylamine are uniformly mixed in a weight ratio of 2:3:4:5:2 to obtain a mixed olefin;
[0071] Weigh: 1000 mL of polysiloxane emulsion is added to a nitrogen-protected reactor and stirred, 165 g of mixed olefins and 2.5 g of potassium persulfate are added to the reactor, the temperature of the reactor is increased to 80°C, and the reactor is kept warm for 7 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, 300 mL of 5 wt% calcium chloride solution is added to the reactor, stirred to break the emulsion, filtered, the filter cake is washed 3 times with purified water and then dried, the filter cake is transferred to a drying oven at a temperature of 65°C, and vacuum dried to constant weight to obtain a reinforced elastomer.
[0072] S3. Preparation of composite fillers
[0073] Calcium carbonate and magnesium hydroxide were added into a ball mill in a weight ratio of 3:1, and the mixture was passed through a 100-mesh sieve to obtain an inorganic mixed powder;
[0074] Weigh: 100g of inorganic mixed powder, 60g of KH-550, and 800mL of ethanol, add them into a reactor and stir and disperse for 40min, raise the temperature of the reactor to 50°C, add 200mL of 0.4mol / L sodium hydroxide solution into the reactor, and keep the reaction for 4h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at 75°C, and vacuum dry it to constant weight to obtain a composite filler precursor;
[0075] Mix sodium bicarbonate and triethylamine in a weight ratio of 1:2 to obtain an acid binding agent;
[0076] 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and chloroform are uniformly mixed in a weight ratio of 1:3 to obtain a 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution;
[0077] Weigh: 100 g of composite filler precursor, 20 g of acid binding agent and 800 mL of chloroform, add into the reactor and stir, lower the temperature of the reactor to 10°C, add 140 g of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution into the reactor, after the addition is complete, keep warm for 40 minutes, raise the temperature of the reactor to 45°C, keep warm for 9 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake twice with chloroform and then three times with purified water, transfer the filter cake to a drying oven at 75°C, and vacuum dry to constant weight to obtain a composite filler.
[0078] S4. Preparation of composite polyethylene
[0079] Dicumyl peroxide and ammonium nitrate are uniformly mixed in a weight ratio of 4:1 to obtain an initiator;
[0080] Mix zinc stearate, polyethylene wax, diisobutyl phthalate and antistatic agent TM in a weight ratio of 3:1:7:2 to obtain an auxiliary additive;
[0081] Weigh out by weight: 95 parts of low-density polyethylene, 10 parts of glycidyl methacrylate, 5.5 parts of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, 18.5 parts of composite filler, 25 parts of reinforced elastomer, 0.6 parts of initiator and 4 parts of auxiliary additives, and mix them evenly to obtain a mixture;
[0082] The mixed material is added into a twin-screw extruder, the temperatures of the six temperature zones from the feed end to the discharge end of the twin-screw extruder are 1850°C, 190°C, 195°C, 195°C, 195°C, and 200°C, respectively, and the main shaft speed of the twin-screw extruder is 16r / min. The mixed material is melt-extruded through the twin-screw extruder to obtain composite polyethylene.
[0083] Example 3
[0084] This embodiment provides a method for preparing a reinforced and toughened composite polyethylene material for plastic pipe processing, comprising the following steps:
[0085] S1. Preparation of modified siloxane
[0086] Weigh: 685.4 g of 18methyl-1,17-dihydroxynonasiloxane and 3427 mL of toluene are added to a nitrogen-protected reactor with stirring. The temperature of the reactor is raised to 60°C. 174.5 g of 3-isocyanate propylene is added to the reactor. The reaction is kept warm for 5 hours. After the reaction is completed, the temperature of the reactor is raised to 90°C, and the solvent is evaporated under reduced pressure to obtain modified siloxane.
[0087] S2. Preparation of reinforced elastomer
[0088] Purified water, ethanol, sodium dodecylbenzene sulfonate, and dodecylphenol polyoxyethylene ether were uniformly mixed in a dosage ratio of 10 mL: 3 mL: 0.3 g: 0.1 g to obtain an emulsion;
[0089] Octamethylcyclotetrasiloxane, 5-hexenyltrimethoxysilane and ethyl orthosilicate are uniformly mixed in a weight ratio of 5:2:1 to obtain a siloxane solution;
[0090] Weigh: 500 mL of the emulsion was added to the reactor and stirred at a stirring speed of 800 r / min. The temperature of the reactor was raised to 75°C. 150 g of the siloxane solution was added dropwise to the reactor. After the addition was complete, the reaction was carried out at the temperature for 6 hours to obtain a polysiloxane emulsion;
[0091] Ethylene glycol dimethacrylate, modified siloxane, N-(4-aminophenyl)maleimide, butyl acrylate and oleylamine are uniformly mixed in a weight ratio of 2:3:4:5:2 to obtain a mixed olefin;
[0092] Weigh: 1000 mL of polysiloxane emulsion is added to a nitrogen-protected reactor and stirred, 180 g of mixed olefins and 3 g of potassium persulfate are added to the reactor, the temperature of the reactor is increased to 85°C, and the reactor is kept warm for 8 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, 300 mL of 5 wt% calcium chloride solution is added to the reactor, stirred to break the emulsion, filtered, the filter cake is washed 3 times with purified water and then dried, the filter cake is transferred to a drying oven at a temperature of 70°C, and vacuum dried to constant weight to obtain a reinforced elastomer.
[0093] S3. Preparation of composite fillers
[0094] Calcium carbonate and magnesium hydroxide were added into a ball mill in a weight ratio of 3:1, and the mixture was passed through a 100-mesh sieve to obtain an inorganic mixed powder;
[0095] Weigh: 100g of inorganic mixed powder, 60g of KH-550, and 800mL of ethanol, add them into a reactor and stir and disperse for 50min, raise the temperature of the reactor to 55°C, add 200mL of 0.5mol / L sodium hydroxide solution into the reactor, and keep the reaction for 5h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water for 3 times and then drain, transfer the filter cake to a drying oven at 80°C, and vacuum dry it to constant weight to obtain a composite filler precursor;
[0096] Mix sodium bicarbonate and triethylamine in a weight ratio of 1:2 to obtain an acid binding agent;
[0097] 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and chloroform are uniformly mixed in a weight ratio of 1:3 to obtain a 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution;
[0098] Weigh: 100 g of composite filler precursor, 20 g of acid binding agent and 800 mL of chloroform, add into the reactor and stir, lower the temperature of the reactor to 12 ° C, add 140 g of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution into the reactor, after the addition is complete, keep warm for 50 minutes, raise the temperature of the reactor to 50 ° C, keep warm for 10 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake twice with chloroform and then three times with purified water, transfer the filter cake to a drying oven at a temperature of 80 ° C, and vacuum dry to constant weight to obtain a composite filler.
[0099] S4. Preparation of composite polyethylene
[0100] Dicumyl peroxide and ammonium nitrate are uniformly mixed in a weight ratio of 4:1 to obtain an initiator;
[0101] Calcium stearate, microcrystalline wax, diethyl phthalate and antistatic agent SP are uniformly mixed in a weight ratio of 3:1:7:2 to obtain an auxiliary additive;
[0102] Weigh by weight: 100 parts of low-density polyethylene, 12 parts of glycidyl methacrylate, 6 parts of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, 22 parts of composite filler, 30 parts of reinforced elastomer, 0.8 parts of initiator and 5 parts of auxiliary additives, mix well to obtain a mixture;
[0103] The mixed material is added into a twin-screw extruder, the temperatures of the six temperature zones of the twin-screw extruder from the feed end to the discharge end are 1850°C, 190°C, 195°C, 195°C, 195°C, and 200°C, respectively, and the main shaft speed of the twin-screw extruder is 17r / min. The mixed material is melt-extruded through the twin-screw extruder to obtain composite polyethylene.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 3 is that in step S2, N-(4-aminophenyl)maleimide is not added.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 3 is that the composite filler in step S4 is replaced by the composite filler precursor in step S3.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 3 is that nano silicon dioxide is used to replace the inorganic mixed filler in step S3.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 3 is that glycidyl methacrylate is not added in step S4.
[0112] Performance Test:
[0113] The tensile stress at break, tensile strain at break, notched impact strength of simply supported beam, tensile notched impact strength and combustion performance of the composite polyethylene prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to the standard GB / T 1845.2-2021 "Plastic polyethylene (PE) molding and extrusion materials Part 2: Sample preparation and performance determination";
[0114] According to the standard GB / T 7141-2008 "Test Method for Thermal Aging of Plastics", the samples prepared in Examples 1-3 and Comparative Examples 1-4 were placed at a temperature of 70±1°C and an ultraviolet radiation intensity of 260W / m 2 The samples were subjected to heat aging treatment in a heat aging test chamber for 10 days, and then the tensile fracture stress, tensile fracture strain, simply supported beam notched impact strength and tensile notched impact strength of the aged samples were tested according to the standard GB / T 1845.2-2021 "Plastic Polyethylene (PE) Molding and Extrusion Materials Part 2: Specimen Preparation and Performance Determination". The specific test results are shown in Table 1 below.
[0115] Table 1-Performance test data of samples before aging
[0116] Data Analysis:
[0117] Comparative analysis of the data in Table 1 above shows that the tensile fracture stress of the composite polyethylene prepared by the present invention reaches 38.2 MPa, the tensile fracture strain reaches 522.1%, and the simply supported beam notched impact strength reaches 110.2 kJ / m 2 The combustion grade reaches V-0. After aging treatment, the tensile fracture stress of the material reaches 36.7MPa, the retention rate reaches 96.1%, the tensile fracture strain reaches 490.8%, the retention rate reaches 94.0%, and the simply supported beam notch impact strength reaches 105.1kJ / m 2 , the retention rate reached 95.4%, and all performance test data were better than the control ratio;
[0118] The method is to prepare a reinforced elastomer by coating polysiloxane with polyolefin, use specially treated calcium carbonate and magnesium hydroxide as composite fillers, and use glycidyl methacrylate as a cross-linking aid. The low-density polyethylene and flame retardant system are reinforced under the action of an initiator. This not only effectively improves the tensile properties and impact toughness of the composite polyethylene material, but also improves the flame retardant and aging resistance of the material, making the composite polyethylene material more suitable for the processing and preparation of outdoor pipes.
[0119] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A reinforced and toughened composite polyethylene material for plastic pipe processing, characterized in that: The invention comprises the following components in parts by weight: 90-100 parts of low-density polyethylene, 8-12 parts of glycidyl methacrylate, 5-6 parts of flame retardant, 15-22 parts of composite filler, 20-30 parts of reinforced elastomer, 0.5-0.8 parts of initiator and 3-5 parts of auxiliary additives; The flame retardant is N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine; The reinforced elastomer is obtained by processing the following steps: A1. Add the emulsion to a reactor and stir. Raise the temperature of the reactor to 65-75°C, add a siloxane solution dropwise to the reactor, and keep the temperature for 4-6 hours to obtain a polysiloxane emulsion, wherein the emulsion and the siloxane solution are in a ratio of 10 mL:2-3 g, the siloxane solution is composed of octamethylcyclotetrasiloxane, 5-hexenyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 5:2:1, and the emulsion is composed of purified water, ethanol, sodium dodecylbenzene sulfonate and dodecylphenol polyoxyethylene ether in a ratio of 10 mL:3 mL:0.3 g:0.1 g; A2. Under nitrogen protection, a mixed olefin and an initiator are added to a reactor containing a polysiloxane emulsion, the temperature of the reactor is raised to 75-85° C., the reactor is kept warm for 6-8 hours, and a reinforced elastomer is obtained by post-treatment, wherein the amount ratio of the polysiloxane emulsion, the mixed olefin and the initiator is 100 mL: 15-18 g: 0.2-0.3 g, the mixed olefin is composed of ethylene glycol dimethacrylate, modified siloxane, N-(4-aminophenyl) maleimide, butyl acrylate and oleylamine in a weight ratio of 2:3:4:5:2, and the initiator is potassium persulfate; The composite filler is processed by the following steps: B1, adding calcium carbonate and magnesium hydroxide in a weight ratio of 3:1 into a ball mill, grinding, passing through a 100-mesh sieve, to obtain an inorganic mixed powder; B2. Add the inorganic mixed powder, KH-550 and ethanol into the reactor and stir and disperse for 30-50 minutes. Raise the temperature of the reactor to 45-55°C, add the catalyst into the reactor, keep the temperature for 3-5 hours, and post-treat to obtain the composite filler precursor. B3. Add the composite filler precursor, acid binding agent and chloroform into the reactor and stir. Lower the temperature of the reactor to 8-12°C, add 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution into the reactor, and after the addition is complete, keep the temperature for 30-50 minutes. Increase the temperature of the reactor to 40-50°C, keep the temperature for 8-10 hours, and perform post-treatment to obtain the composite filler.
2. The reinforced and toughened composite polyethylene material for plastic pipe processing according to claim 1, characterized in that: The initiator is composed of dicumyl peroxide and ammonium nitrate in a weight ratio of 4:1, the auxiliary additives are composed of a dispersant, a lubricant, a plasticizer and an antistatic agent in a weight ratio of 3:1:7:2, the dispersant is stearate, the lubricant is one or more of ethylene bisstearamide, polyethylene wax, and microcrystalline wax, the plasticizer is phthalate, and the antistatic agent is one or more of antistatic agent SN, antistatic agent TM, and antistatic agent SP.
3. The reinforced and toughened composite polyethylene material for plastic pipe processing according to claim 1, characterized in that: The preparation method of modified siloxane is as follows: 18methyl-1,17-dihydroxynonasiloxane and toluene are added into a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 50-60°C, 3-isocyanate propylene is added into the reactor, the reaction is carried out for 3-5 hours, and the modified siloxane is obtained by post-treatment.
4. The reinforced and toughened composite polyethylene material for plastic pipe processing according to claim 3, characterized in that: The usage ratio of 18methyl-1,17-dihydroxynonasiloxane and 3-isocyanate propylene is 1 mol:2.1 mol.
5. The reinforced and toughened composite polyethylene material for plastic pipe processing according to claim 1, characterized in that: In step B2, the amount ratio of the inorganic mixed powder, KH-550, ethanol and catalyst is 5g:3g:40mL:10mL, and the catalyst is 0.2-0.5mol / L sodium hydroxide solution; in step B3, the amount ratio of the composite filler precursor, acid binding agent, chloroform and 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution is 5g:1g:40mL:7g, the acid binding agent is composed of sodium bicarbonate and triethylamine in a weight ratio of 1:2, and the 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride solution is composed of 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and chloroform in a weight ratio of 1:
3.
6. The method for preparing the reinforced and toughened composite polyethylene material for plastic pipe processing according to any one of claims 1 to 5, characterized in that: The preparation method of the reinforced and toughened composite polyethylene material for plastic pipe processing is as follows: low-density polyethylene, glycidyl methacrylate, flame retardant, composite filler, reinforced elastomer, initiator and auxiliary additives are added into a twin-screw extruder for melt extrusion to obtain composite polyethylene.
7. The method for preparing a reinforced and toughened composite polyethylene material for plastic pipe processing according to claim 6, characterized in that: The temperatures of the six temperature zones of the twin-screw extruder from the feed end to the discharge end are 1850°C, 190°C, 195°C, 195°C, 195°C, and 200°C, respectively, and the main shaft speed of the twin-screw extruder is 15-17r / min.
Citation Information
Patent Citations
Reinforced polyethylene pipe material and preparation method thereof
CN112662111A
High-toughness and high-strength polyolefin pipeline and preparation method thereof
CN106366414A
Toughened modified material for PE pipes and preparation method thereof
CN110734598A